Audio Description with Audio Subtitling for Dutch Multilingual Films: Manipulating Textual Cohesion on Different Levels - Remael, Aline (Meta, 2012)
There is a strong trend towards multilingualism in Flemish and Dutch films today. In order to make such films accessible for a blind and visually impaired audience, the audio description (AD), which supplies the information from the visuals that cannot be accessed by this target audience, must be combined with audio subtitling (AST), for the translation of the dialogue. Today, a wide variety of strategies is used to accomplish this form of textual manipulation, but current practice is largely based on intuition. The present paper reports on the first phase of a research project carried out on four films, in collaboration with the AD scriptwriter and the sound engineer responsible for the recordings of the Dutch films with AD and AST, two of which will be considered here: Oorlogswinter (Winter in Wartime 2008) and Tirza (2010). The project makes use of four films, but due to limits of space we focus on two only, aiming to reply to three questions. First, we look at how the AST is inserted and whether it interacts with the films’ foreign language dialogue exchanges. Then we consider whether intonation contributes to the coherence of the text. To conclude, the audio and written subtitles are compared. Finally, suggestions for further research are provided.